PARADOX OFMARKETINGTOTHE PHYSICALLYCHALLENGED INDIVIDUALS - SUSTAINABLE DIFFERENTIATION OR SIMPLY MARKETING HYPE - RAHMAN, SYAFIQUR (ITB Journal Publisher, LPPM ITB, 2009)
It has long been acknowledged that service differentiation through effective market segmentation ensures survivability of the firm in the long run. While voluminous studies on segmentation and providing service differentiation were conducted, little previous research work was done in the context of the airline industry. It is the intention of this paper to examine the needs of the physically challenged individuals and the reasons constraining the industry in fulfilling these needs. This paper will contribute significantly to understanding the needs of the physically challenged individuals and suggest that meeting the needs of these individuals provide sustainable competitive advantage for those who dare to adapt their strategy. Given the little previous researches were conducted in the identification of this potential group of customers, it is no wonder the airline industry is myopic and ill-prepared in meeting the needs of this viable group of customers. This study is also beneficial from a managerial perspective given the implications in assisting the airline operators and marketers to better understand this group of customers and their needs. Particularly specific features identified in this paper can help increase the overall position of airline operators that would appeal to this growing segment.